Nanofiltration Membrane For Water Purification Pretreatment And Its Fouling Phenomena - Ramanathan, Geetha (2017)
In water treatment processes, membrane fouling is one of the main drawbacks of membrane technology. Membrane fouling causes flux declination and reduces the treated water quality. This study aims to evaluate the fouling behavior of nanofiltration membranes with respect to the pretreatment process and to determine the best practice of membrane cleaning process. The feed water was introduced as solution before and after 3.00 μm pre-filtration and also after combination of 3.00 and 0.45 μm pre-filtration. The bench scale cross flow filtration were conducted to evaluate the efficiency of water pretreatment processes. Water treatment was carried out by using commercially available nanofiltration membrane (NF90 and NF270) with and without polyaluminium chloride as coagulant dosage in feed water. It was found that NF270 is more fouling resistance compared to NF90 due to its hydrophilicity characteristic with contact angle of 7.15 and smoother membrane surface with membrane roughness of 18.78 nm. The fouling rate of NF90 with PAC dosage was reduced from 24% to 18% after 3.00 μm and 0.45 μm pre-filtration. However, without PAC lower fouling rate of 12% can be achieved. NF270 membrane process with or without PAC gave insignificant flux reduction. In overall, NF 90 membrane without PAC with combination of 3.00 and 0.45 μm pre-filtration gave better permeate water quality of 0.5 MΩ due to NF90’s tighter pore size. 0.5 Mol/L of NaOH was required to achieve cleaning efficiency of 76%. The water that is produced during filtration process complies with the standard and is suitable to be used as feed to reverse osmosis (RO) membrane.